Mechano‐optical behavior in poly (ethylene terephthalate)/poly (ether imide) blends. Issue 18 (28th July 2021) - Mutlu, Zeynep; Jain, Mayank; Yook, Sung Ho; Cakmak, Mukerrem
Abstract: Mechano‐optical behavior and related structural evolution during uniaxial stretching of melt miscible poly (ethylene terephthalate) (PET)/poly (ether imide) (PEI) blends were studied near their glass transition temperature using an instrumented machine that measures true stress, true strain and spectral birefringence simultaneously. Stretching from amorphous state, two distinct stress‐optical regimes were observed at temperatures between Tg and Tcc (cold crystallization). Near Tg, a typical photoelastic behavior persists until a critical temperature above which temperature independent initial stress optical behavior is observed. At those temperatures above Tg, where glassy behavior is observed, decreasing stretching rate was also found to eliminate this glassy photo elastic regime leading to the observation of a linear initial stress optical behavior that becomes temperature independent as expected from linear stress optical rule. Increasing PEI concentration in the blends suppresses crystallizability and increases temperature at which initial elastic region disappears giving way to pure liquid behavior where linear stress optical behavior is observed. This is attributed to the increase and broadening of the glass transition temperature with the addition of noncrystallizable PEI. In PET/PEI blends, the stress‐optical coefficient (SOC), determined in a linear stress optical regime, was found to increase linearly with the increase in PEI concentration. Abstract :